Visual field survival: the response to timolol therapy in open-angle glaucoma. - Sponsel, W. E. (1983)
A simple method for quantifying visual field survival was devised to assess the progress of chronic simple glaucoma in 36 patients treated with timolol maleate over a 3-year period. Routine tonometric monitoring of the intraocular pressure (IOP) was carried out in conjunction with these Goldmann field studies. Statistical analysis revealed that field survival measurement provided a more consistent clinical guide to the progress of glaucoma under treatment than did IOP (p much less than 0.001). Timolol therapy was associated with sustained IOP reductions of 24.3-34.5%, and 63% of those treated who were monitored for field survival showed no significant field loss. The observed relationships of IOP to field survival are discussed.